Generation of deletion derivatives by targeted transformation of human-derived yeast artificial chromosomes. - Pavan, W J (1990)
Mammalian DNA segments cloned as yeast artificial chromosomes (YACs) can be manipulated by DNA-mediated transformation when placed in an appropriate yeast genetic background. A "fragmenting vector" has been developed that can introduce a yeast telomere and selectable marker into human-derived YACs at specific sites by means of homologous recombination, deleting all sequences distal to the recombination site. A powerful application of the method uses a human Alu family repeat sequence to target recombination to multiple independent sites on a human-derived YAC. Sets of deletion derivatives generated by this procedure greatly facilitate restriction mapping of large genomic segments. Targeting recombination with single copy sequences, such as cDNAs, will have many additional applications. This approach establishes a paradigm for manipulation and characterization of mammalian DNA segments cloned as YACs.